PENGARUH SENAM JANTUNG SEHAT SERI-I TERHADAP DAYA TAHAN JANTUNG-PARU, KEKUATAN OTOT DAN KADAR TNF-α PLASMA PADA LANJUT USIA - Ajeng Fitria; Leonardo Lubis; Ambrosius Purba (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2019)
The increasing number of elderly and elderly life expectancy is a challenge for health workers. Decreased cardiac endurance, muscle strength and increased incidence of inflammation will occur in the elderly as we get older. health cardio exercises series-I is an aerobic exercise that has moderate intensity and is carried out for 30 minutes, research is needed to analyze the effect on cardiac endurance, muscle strength and decrease plasma TNF-α levels in the elderly. Research design with experimental method, pre-test and posttest design approach. The study was conducted for 4 weeks on 25 samples which were divided into 3 groups of frequency of health cardio exercises series-I to measure endurance of the heart. A 6-minute road test and muscle strength were used for hand grip strength dynamometer, test back and leg dynamometer. Measurement of plasma TNF-α levels is carried out using the Elisa method. The data was then analyzed using paired t-test to see differences before and after health cardio exercises series-I. The results showed health cardio exercises series-I performed 3x / mg can increase the heart's endurance compared to the frequency of 4x / mg and 5x / mg (-16.11 vs 15.62 vs -47.62 meters). health cardio exercises series-I frequency of 3x / mg and 4x / mg can increase back muscle strength (pvalue= 0.019, p <0.05) and the frequency of 5x /mg can increase the strength of attractive shoulder muscles. (p-value=0.033, p<0.05). Health cardio exercises series-I performed 3x / mg, 4x / mg and 5x / mg did not have a significant effect on plasma TNF-α protein expression in the elderly (0.506 vs 0.856 vs. 0.382, p<0.05). It is suggested that the elderly can do I-1 series heart exercise with a frequency of 3x / mg to increase the heart's lung endurance and back muscle strength, a health cardio exercises series-I 4x / mg series to increase muscle strength of the back back, a series of health cardio exercises series-I frequency of 5x / mg to increase attractive shoulder muscle strength.